Bembé de Sao desde la familia Rousseaux Durruty - Enríquez Rodríguez, Yoel (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
This work shows musical features developed by the family Rousseaux Durruty, at the beginning of the 1970’s several members of this family emigrated to the west Cuban town hall of Melena del Sur, coming from Guantánamo, the most easterly region of the isle. They brought with them their cultural practices unknown in the context where they arrived. The Muertería Oriental is the phenomenon of the popular religiosity that is in the eastern area of Cuba whose festive moment is called Bembé de Sao. The relocation of its traditions has promoted the internal and external trans-culturative processes. The family shows musical instruments of its elaboration, whose character is ritual. Also, they are presented various of the songs recollected during the field of work, as well as they are established analytical parallelism that develop in the main isle of the Caribbean islands.